2011
DOI: 10.1002/pbc.23010
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of overweight in pediatric survivors of acute lymphoblastic leukemia (ALL)

Abstract: Many children with ALL gain weight during therapy and fail to return to normal weight after treatment concludes. Subsequent diet, physical activity, and sedentary behavior do not appear to differ between overweight and normal weight survivors. Clinicians should focus on ways to minimize weight gain during therapy rather than waiting for treatment to conclude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 47 publications
5
38
1
1
Order By: Relevance
“…10,11,14,34,47,51,60 However, the other 15 studies did not find evidence of a gender difference. [6][7][8]12,15,28,31,33,36,38,47,[52][53][54]62 FIGURE 2…”
Section: Obesity In Pediatric All Survivors By Patient and Treatment mentioning
confidence: 64%
See 3 more Smart Citations
“…10,11,14,34,47,51,60 However, the other 15 studies did not find evidence of a gender difference. [6][7][8]12,15,28,31,33,36,38,47,[52][53][54]62 FIGURE 2…”
Section: Obesity In Pediatric All Survivors By Patient and Treatment mentioning
confidence: 64%
“…Four studies reported that being overweight/obese or having a high BMI z score at diagnosis was associated with a high prevalence of obesity. 10,30,51,52 However, 1 study found a low BMI z score at diagnosis predicted obesity after treatment completion. 36 …”
Section: Age At Diagnosismentioning
confidence: 88%
See 2 more Smart Citations
“…Research on overweight prevalence has involved mostly ALL survivors (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), whereas study of risk factors has led to inconsistent conclusions (4). Studies conducted in the United States reflect the lifestyles and eating habits of CSSs in that country (10-13, 16, 17, 19-22), whereas the duration of follow-up in other studies has been only short to medium term (4,5), and many have had small (<250 participants) sample sizes (4,11,(13)(14)(15)(17)(18)(19). With this background of research in mind, we analyzed data from the Swiss Childhood Cancer Survivor Study (SCCSS) to 1) assess overweight prevalence in CCSs overall and for specific, different diagnoses; 2) compare overweight prevalence in CCSs with that in their siblings and the Swiss general population; and 3) identify sociodemographic and clinical risk factors for excessive weight.…”
Section: Introductionmentioning
confidence: 99%